Analisis Struktur Ekonomi Kelautan Indonesia - sapanli, kastana; Kusumastanto, Tridoyo; Budiharsono, Sugeng; sadelie, Agus (JURNAL MINA SAINS, 2019)
Marine economy is an economic activity carried out in the sea and land areas whose activities are still related to marine resources. The marine sector is defined as seven sectors, namely: fisheries, marine tourism, mining, marine industry, sea transportation (marine transportation), marine building, marine services. This study used descriptive and impact analysis in the national Input-Output Table in 2010. The total output of the marine sector accounted for 27.39% of total national output. The GDP value in the marine sector is able to contribute 30.32% of the total national GDP. From the results of calculations regarding the analysis of the multiplier numbers by output, the formation of new output in the economy was 1.4087 units. Analysis of multiplier numbers by job opportunities causes an increase in employment opportunities by an average of 0.1451 units. The majority of the sectors of maritime tourism show high distribution power. The largest sub-sector with a sensitivity index value is the trade service sub-sector, which is 1.4608. Key words: descriptive analysis, impact analysis, marine economy, I-O table